Interaction of common bacterial blight quantitative trait loci in a resistant inter‐cross population of common bean. Issue 6 (23rd September 2013) - Durham, Kelli M.; Xie, Weilong; Yu, Kangfu; Pauls, K. Peter; Lee, Elizabeth; Navabi, Alireza; Link, W.
Abstract Common bacterial blight (CBB), caused by Xanthomonas axonopodis pv. phaseoli, is an important disease of common bean (Phaseolus vulgaris L.). Genetic resistance is the most economically efficient, environmentally friendly and socially acceptable approach to control plant diseases including CBB. To examine the main and interaction effects of the previously identified CBB resistance quantitative trait loci (QTL) associated with markers BC420 (B) on Pv06, SAP6 (S) on Pv10 and PVctt001 (P) on Pv04, in presence of the major QTL associated with the marker SU91 (Su) on Pv08, a resistant F4:5 recombinant inbred line population of the reciprocal crosses between OAC Rex (bb/ss/PP/SuSu) and HR45 (BB/SS/pp/SuSu) was evaluated under artificial field inoculation in disease nurseries in 2009 and 2010. While, in presence of the CBB QTL on Pv08, the QTL on Pv06 of HR45 accounted for 37–46% of phenotypic variation in the field, the effect of QTL on Pv04 and Pv10 were not significant under field conditions, even in the absence of the Pv06 QTL. Broad‐sense heritability estimates of CBB resistance and the QTL associated with BC420 were high for CBB severity and the area under the disease progress curve, promoting the continued efforts in pyramiding the QTL on Pv06 and Pv08 in common background, which provide high levels of resistance.